Psychological wellbeing in adult adoptees: current age and developmental tasks - Melero, Sandra; Verdugo, Laura; Sánchez-Sandoval, Yolanda (Frontiers in Psychology, 2023)
Introduction: Studies about adult adoptees are normally focused on the differences in adjustment difficulties between them and non-adoptees. However, there has been less research about adoptees’ positive and developmental adjustment in adulthood. The aim of this study is to test a model of the mediating role of adoptees’ achievement of adulthood tasks in the relationship between current age and psychological well-being. Materials and methods: The sample consisted of 117 adults who were adopted as children by Spanish families. Their current mean age is 28.3 years. Participants underwent an interview and completed Ryff’s Psychological Well-Being Scales. Results: Findings show that current age is directly and negatively related to psychological well-being (c’ = -.039, 95% CI [-.078, -.001]), and the relationship between these variables is mediated by adoptees’ achievement of adulthood tasks (indirect effect = .035, 95% CI [.014, .059]). Discussion: The findings support traditional theories about transitioning to adulthood, and adds relevant information about this transition in adoptees. Moreover, this work indicates a new way of assessing adoption success, based on long-term measures and normative variables. Services providers should account for the importance of supporting young people on their life transitions and promoting their well-being, especially among those who started from disadvantaged contexts.